The molecular characterisation of Mss11p, a transcriptional activator of the Saccharomyces cerevisiae MUC1 and STA1-3 genes - Gagiano, Marco, 1971- (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2002.